(untitled) (Світ фінансів, 2017)
Двігун А. О. Рентна політика та її роль у реалізації фінансової стратегії держави. Досліджено теоретичні і методологічні засади реалізації рентної політики в економічній системі держави. Виявлено основні закономірності і тенденції, що характеризують процес формування і розвитку рентних відносин в Україні. Сформульовані рекомендації щодо правового регулювання економічних процесів, пов’язаних з рентними відносинами, а також збереженням, ощадливим використанням та відтворенням природних багатств з метою забезпечення конкурентних переваг. Dvigun A. Rental policy and its role in implementation of fi nancial policy of the state. The idealized and methodological fundamentalses of implementation of rental policy in an economical system of the state are investigated. The basic regularity and tendency, which one characterize process of formation and development of rental relations in Ukraine are detected. Guidelines concerning legal regulation of economical processes, bound with rental relations, and also preservation, economical usage and reproduction of natural wealths with the purpose of maintenance of competitive advantages are formulated.